IoT Based Water Quality Control For Small-Scale Aquarium With Fuzzy Logic - Safawati, Annuar (2023)
In order to ensure that aquatic organisms have a healthy and prosperous environment, this abstract introduces a water quality system that was especially created for aquariums. The system uses several sensors to continuously track important factors like temperature, pH level, and water level. Real-time data from these sensors is processed and analysed using a fuzzy logic-based methodology. The fuzzy logic system evaluates the water quality conditions and decides on the proper course of action to maintain ideal conditions inside the aquarium using membership functions and rules. The technology automatically controls crucial elements including filtration, and water replacement, reducing stress on aquatic life, and streamlining aquarium maintenance. To demonstrate the system's capacity to continually preserve ideal water quality standards, advance the welfare of aquatic species, and improve aquarium environment management, experimental studies are carried out to confirm its efficacy. Overall, this aquarium water quality system provides a thorough way to keep track of and regulate key variables, maintaining a stable and favourable environment for aquatic life. The system offers an intelligent and automated method for maintaining ideal water quality conditions, eventually improving the health and vitality of the aquarium environment. It does this by utilising fuzzy logic principles.